1989
DOI: 10.1161/01.res.65.4.971
|View full text |Cite
|
Sign up to set email alerts
|

Subendomyocardial exhaustion of blood flow reserve and increased fibrosis in conscious dogs with heart failure.

Abstract: The effects of near-maximal coronary vasodilation were examined in conscious dogs with left ventricular (LV) failure after pressure overload hypertrophy induced by either aortic banding alone or aortic banding plus a peripheral arteriovenous shunt. The findings were compared with results in littermates with compensated LV hypertrophy and with a third group of normal dogs. At rest, there was a marked difference in the intramyocardial distribution of coronary flow, measured with radiolabeled microspheres. The en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
2
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 11 publications
6
65
2
1
Order By: Relevance
“…Coronary flow reserve (CFR), as estimated by the hyperemic/baseline coronary velocity ratio (H/B) as isoflurane is increased from 1.0% to 2.5%, is virtually absent 21 days after aortic banding. Similar reductions in CFR have been reported in dogs with cardiac hypertrophy induced by aortic banding (Parrish et al, 1985;Hittinger et al, 1989), and in humans with aortic stenosis (Marcus et al, 1982).…”
Section: Reduction In Coronary Flow Reservesupporting
confidence: 69%
See 3 more Smart Citations
“…Coronary flow reserve (CFR), as estimated by the hyperemic/baseline coronary velocity ratio (H/B) as isoflurane is increased from 1.0% to 2.5%, is virtually absent 21 days after aortic banding. Similar reductions in CFR have been reported in dogs with cardiac hypertrophy induced by aortic banding (Parrish et al, 1985;Hittinger et al, 1989), and in humans with aortic stenosis (Marcus et al, 1982).…”
Section: Reduction In Coronary Flow Reservesupporting
confidence: 69%
“…Similarly high systolic velocities with an average S/D of 0.7 can been seen in the Doppler waveforms and data presented by Hozumi, et al (1998) from the LAD coronary arteries of patients with aortic valve disease. Indeed, it has been found in patients and experimental animals that there is relative subendocardial underperfusion and ischemia with pressure overload cardiac hypertrophy (Marcus, 1983;Hittinger et al, 1989;Hittinger et al, 1995), and subendocardial ischemia has been proposed as one of the precipitating factors leading to decompensated heart failure (Parrish et al, 1985;Vatner and Hittinger, 1993).…”
Section: Increase In Systolic Coronary Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, radial thickening is influenced by the complex 3-dimensional fiber rearrangement in the LV wall [27]. In dogs with severe LV hypertrophy, exhaustion of subendocardial blood flow reserve is associated with myocyte necrosis and fibrosis, demonstrating that structural alterations play an important role in the development of heart failure [28]. Poulsen et al [29] showed that reduced longitudinal strain is associated with increased collagen turnover and degree of myocardial fibrosis in hypertensive patients.…”
Section: Impaired Endocardial Radial Strain In Hypertensive Patients mentioning
confidence: 99%